Otomatisasi Penyiraman Tanaman Cabai Dan Tomat Berbasis Iot - Nurul Fauzia, Nur Kholis, Humaidillah Kurniadi Wardana (Reaktom : Rekayasa Keteknikan dan Optimasi, 2021)
Watering plants on agricultural land by applying IoT application that can be monitored on smartphone is veri necessary for farmers to faciliitate farmers to monitor and care for plants easily, effectively and efficiently. The purpose of this research to design and make watering devices for chili and tomato plants that can watering automatically IoT based. The research method used is an experimental method designed using esp32 as the main control module of the system, humidity sensor YL-69 to measure soil moisture, ultrasonic sensor HCSR-04 to control water availability in reservoirs, and blynk application as a display on smartphone. The result of research on the design of automatic watering on chili and tomato plants carried out for 3 consecutive days starting at 07:00 WIB to 17:00 WIB. The result of research on the design of watering plants for chilies and tomatoes can function well and can work with adc values of > 600 pumps on up to < 600 pumps off.